Resilient event-triggered model predictive control for adaptive cruise control under sensor attacks - Hu, Zhijian (2023)
This letter addresses the resilient model predictive control (MPC) problems for adaptive cruise control (ACC) systems under sensor attacks. In the light of vulnerabilities of ACC systems to sensor attacks, an intrusion detection mechanism is proposed at the controller side to distinguish abnormal data. Then, the robust control gains are derived to design the terminal region constraint for MPC. Further, an improved event-triggered scheme is presented, which shows the ability to relieve the computation burden in the implementation of MPC, by combining the memory-based event-triggered condition and the maximum allowed time interval condition. Finally, efficacy validations are given in simulations.